PENGARUH MODEL COOPERATIVE LEARNING TIPE JIGSAW BERBANTUAN MEDIA LAPBOOK TERHADAP PEMAHAMAN KONSEP KEARIFAN LOKAL - Shely Handayani; Sofyan Iskandar; Jennyta Caturiasari3 (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The study is motivated by the influence of the Cooperative Learning model of the Jigsaw type, assisted by Lapbook media, on the understanding of local wisdom concepts among fourth-grade students. Based on descriptive analysis, the pretest results showed an average score of 67.24 with a standard deviation of 10.904, indicating the students' initial understanding was relatively low. After the intervention, the posttest average score increased to 84.65 with a standard deviation of 9.629, showing a significant improvement of 17.41 points. Normality and homogeneity tests confirmed the data were normally distributed and the variance among groups was homogeneous. The results of the Paired Sample T-Test demonstrated a significant difference between pretest and posttest scores (Sig. < 0.001), while a simple linear regression test revealed a positive and significant effect of the Jigsaw model on the understanding of local wisdom concepts, with an R² value of 0.651. Additionally, the N-Gain score was 0.56 (moderate category), and effectiveness was measured at 56% (moderately effective). Thus, the Cooperative Learning model of the Jigsaw type, assisted by Lapbook media, significantly influences students' understanding of local wisdom concepts.